PENGENALAN, DETEKSI DINI KANKER SERVIX DAN PAYUDARA WANITA USIA SUBUR DAN MENOPAUSE - Nur Chayati; Arianti Arianti (Universitas Muhammadiyah Yogyakarta, 2018)
This society activities have a purpose for introducing about cancer for the woman population. Population target are fertility and menopouse woman . The partner of this activities is woman group from distric Ngrame, Tamantirto, Kasihan, Bantul. The special target which achieved is improving knowledge of the community about cancer, early detection of cancer physically and through macroscopic test through IVA test (Acetat Visual Inspection) and Pap Smear. Methods that used are health education, training and counseling. Health education are giving with speech method, initially by pre-test for knowing the basic knowledge. This activities than continued with material delivery and discussion. The main topics are about the definition of cancer, abnormality in patient with cancer, risk factors, the caused, pathway of cancer, treatment and prevention of cancer. This activity hold for two times. The next agenda is breast self-examination practice (SADARI), starting with demonstration session by the expertise, then the member will act breast examination by themselves accompany by fascilitators/ kader. At the end, the member are given post-test for evaluating. Final agenda is IVA test, 20 people involved. The result of this test, if the cervix appearance is clean, no mucosal erosion, the participant should reevaluation one year again. If there is mucosal erosion of the cervix, the participant will refer to hospital for take Pap Smear test and must take examination again in one month after in Primary Health Services. Identified 1 mother positive IVA test, and according to Pap Smear result, she got Cervical Cancer Grade IV.